Graphene copper wire composite insulation varnish, and preparation method and coating process thereof
Patent Information
- Application Number
- CN202611196703.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]针对上述背景技术中提到的问题,本发明的目的在于提供一种石墨烯铜线复合绝缘包漆及其制备方法与涂覆工艺,解决传统绝缘漆附着力差、高温易老化、超低温易脆裂、两类线材漆料无法通用的行业痛点,简化生产流程,降低绝缘包覆生产成本,提升高端电磁线材整体绝缘可靠性与服役寿命
本发明中,以正硅酸乙酯作为硅源,经溶胶凝胶法制备得到球形纳米二氧化硅,以球形纳米二氧化硅为内核,在内核表面包覆一层纳米氧化铝过渡壳层,并且通过硅烷水解接枝反应,过渡壳层外侧接枝改性有柔性有机硅长链官能团,形成无机核-无机过渡壳-柔性有机功能层的三级复合结构,而且经过硅烷偶联剂表面活化改性,表面分布高密度活性羟基与环氧活性基团,颗粒无团聚、单分散性优异,从而使得得到的有机功能化纳米填料可以很好的分散在树脂基体中;通过向树脂基体中引入有机功能化纳米填料,表面接枝的有机功能层携带大量活性羟基、环氧活性基团,在漆膜固化过程中,活性基团可分别与线材基材表面的金属羟基、石墨烯表面的含氧基团、树脂基体的共聚活性基团发生共价键交联反应,形成“线材基材-纳米复合材料-树脂基体”的一体化共价键合网络,界面结合强度大幅提升,从分子层面实现高强度粘接锚固,从而有助于提高漆膜的附着力和稳定性;而且,高度分散的有机功能化纳米填料粒径极小,可渗透嵌入石墨烯铜线表面的微观孔隙、超导线材的基材微纹理中,形成微纳机械嵌合结构,增大漆膜与基材的有效接触面积,从而进一步提升漆膜的附着力与剥离强度;同时,有机功能化纳米填料表面的有机硅柔性长链具备优异的超低温柔性,在树脂基体低温收缩、微观形变时,柔性链段可通过自身伸缩、扭转、滑移吸收并释放漆膜内部的集中内应力,避免应力堆积产生微裂纹,起到微观增韧、应力缓冲的核心作用,可以避免漆膜在超低温下产生微裂纹,而且球形纳米二氧化硅刚性内核具备极低的低温热膨胀系数,超低温环境下尺寸几乎无变化,可在漆膜微观体系中构建稳定的刚性支撑骨架,约束改性树脂基体的低温剧烈收缩行为,大幅降低漆膜整体低温收缩率,从源头减少收缩形变产生的内应力,并且刚性内核与柔性有机层之间还形成以后过渡壳层,通过热膨胀系数与力学模量的梯度过渡,消除了无机刚性内核与有机柔性基体之间的物性断崖差异,将原有的界面应力突变转化为平缓梯度应力分布,而且氧化铝壳层丰富的表面羟基构建致密共价键合界面,消除界面微孔隙与脱粘缺陷,杜绝超低温工况下界面微裂纹的萌生、扩展与贯通,从而进一步避免漆膜低温开裂问题的发生。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic insulation materials technology, specifically to a graphene-copper wire composite insulating enamel coating, its preparation method, and coating process. Background Technology
[0002] With the rapid development of new energy power equipment, high-frequency electromagnetic equipment, and superconducting power technology, graphene composite conductive copper wire, low-temperature superconducting wire, and high-temperature superconducting tape have gradually achieved industrial application.
[0003] Graphene composite copper wire has advantages such as high conductivity, excellent heat dissipation performance and lightweight, and is widely used in high-speed motors and energy-saving transformer windings. However, the surface of graphene has stable chemical properties and low surface energy, exhibiting strong hydrophobic characteristics. Conventional polyurethane insulating varnish and ordinary polyimide varnish on the market are difficult to spread evenly on its surface, and the varnish film is prone to defects such as pinholes, peeling, and insufficient adhesion. Under long-term high-temperature operation, the insulation layer ages quickly, shortening the service life of the wire.
[0004] Superconducting wires are classified into NbTi low-temperature superconducting wires, Nb3Sn superconducting wires, and YBCO high-temperature superconducting tapes. These wires are used in ultra-low temperature environments of liquid helium (4.2K) and liquid nitrogen (77K) for extended periods. They are also subjected to strong electromagnetic field impacts and frequent alternating hot and cold conditions. Traditional acetal insulating varnish is highly brittle at low temperatures and is prone to cracking and insulation layer peeling after hot and cold cycles, which can cause safety hazards such as malfunction and leakage in superconducting equipment.
[0005] Currently, graphene copper wire insulation varnish and superconducting wire low-temperature insulation varnish are two independent systems in the industry. The raw material formulas, production equipment and coating processes are not interchangeable. Enterprises have to invest heavily in production line construction, have complicated material management, and have high production costs. The market urgently needs a general composite insulation varnish that can be adapted to both types of high-end wires, and can take into account both high temperature heat resistance and thermal conductivity and ultra-low temperature tough insulation, as well as a matching integrated and mature coating process. Summary of the Invention
[0006] In view of the problems mentioned in the background art above, the purpose of this invention is to provide a graphene copper wire composite insulation coating and its preparation method and coating process, which solves the industry pain points of poor adhesion of traditional insulation coatings, easy aging at high temperatures, easy brittleness at ultra-low temperatures, and incompatibility between the two types of wire coatings, simplifies the production process, reduces the production cost of insulation coating, and improves the overall insulation reliability and service life of high-end electromagnetic wires.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A graphene-copper wire composite insulating varnish, wherein the composite insulating varnish is composed of the following raw materials in parts by weight: 56-64 parts modified resin, 11-18 parts functional thermally conductive filler, 5-10 parts organic functionalized nanofiller, 3-6 parts low-temperature toughening modifier, 2-5 parts thermo-oxidative stabilizing agent, 1-2.5 parts interface adhesion promoter, 0.4-1.6 parts rheology modifier, and 32-46 parts mixed organic solvent.
[0008] As a further preferred embodiment of the present invention, the modified resin is a blend of polyimide and polyvinyl butyral; The functional thermally conductive filler is composed of graphene nanosheets, nano-alumina, and hexagonal boron nitride in a mass ratio of 1:1:(1.0-1.8). The low-temperature toughness modifier is carboxyl-terminated butadiene-acrylonitrile rubber; The thermo-oxidative stabilizer is nano-cerium dioxide powder; The interface adhesion promoter is silane coupling agent KH-560; The rheology modifier is fumed silica. The mixed organic solvent is prepared by combining N-methylpyrrolidone and xylene in a volume ratio of (2.0-2.5):1.
[0009] As a further preferred embodiment of the present invention, the method for preparing the organic functionalized nanofiller is as follows: 1) Spherical nano-silica is ultrasonically dispersed in a mixed solvent to obtain a dispersion with a solid content of 5-8 wt%. Then, a 10-12% (w / w) aluminum sec-butoxide ethanol solution is slowly added dropwise to the dispersion, and a 2-3 mol / L ammonia solution is added dropwise simultaneously to adjust the pH to 8.5-9.0. The temperature is then raised to 55-60℃ and stirred for 3-5 hours. After the reaction is completed, the mixture is centrifuged, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a silica composite alumina intermediate. 2) Disperse the silica-alumina composite intermediate in anhydrous toluene solvent to obtain a suspension with a mass fraction of 8-10%. Slowly add the weighed modifier to the suspension, stir thoroughly, and place it in a reaction vessel. In a high-purity nitrogen atmosphere, heat to 80-90℃ and stir in a closed container at 350-400 r / min for 4-6 h. 3) After the reaction is complete, allow the mixture to cool naturally to room temperature. After centrifugation, wash the mixture repeatedly with anhydrous ethanol and deionized water. Then, spread the obtained product evenly in a crucible and place it in a vacuum drying oven. Perform constant temperature vacuum annealing for 2-3 hours. After ultrafine grinding, pass the product through a 2000-mesh sieve to obtain the desired organic functionalized nanofiller.
[0010] Furthermore, in step 1), the mixed solvent is composed of anhydrous ethanol and ultrapure water in a volume ratio of (5-6):1; The mass ratio of the sec-butoxide aluminum ethanol solution to the dispersion is (0.8-0.9):1; The slow dripping rate is 0.8-0.9 mL / min; The rotation speed of the constant-temperature stirring reaction is 30-50 r / min.
[0011] Furthermore, in step 2), the modifier is obtained by compounding methyltriethoxysilane and 3-glycidyl etheroxypropyltriethoxysilane in a mass ratio of (2.0-2.5):1; The mass ratio of the modifier to the silica-alumina composite intermediate is 1:(4-6). The stirring speed is 350-400 r / min.
[0012] Furthermore, in step 3), the temperature of the vacuum annealing process is 120-125℃, and the vacuum degree is ≤-0.09MPa.
[0013] As a further preferred embodiment of the present invention, the method for preparing the spherical nano-silica is as follows: 1) Measure anhydrous ethanol and ultrapure water, add them to the reaction vessel in sequence, stir thoroughly at room temperature, and slowly add ammonia water with a concentration of 14-16 mol / L to adjust the pH of the system to 10.5-11.0 to obtain a buffer solution. Then slowly add tetraethyl orthosilicate to the buffer solution and stir evenly to obtain the reaction solution. 2) Transfer the reaction solution to a reaction vessel, seal it, and stir the reaction at a constant temperature of 25-28℃ for 4-6 hours. After the reaction is completed, separate it by centrifugation, wash it repeatedly with anhydrous ethanol and deionized water, and then dry it to obtain spherical nano-silica.
[0014] Furthermore, the volume ratio of the anhydrous ethanol to the ultrapure water is (8-10):(2-3). The mass ratio of tetraethyl orthosilicate to buffer solution is 1:(10-12). The slow dripping rate is 1.0-2.0 mL / min; The stirring speed is 400-500 r / min.
[0015] A method for preparing graphene-copper wire composite insulating enamel includes the following steps: (1) Powder modification pretreatment: According to the weight parts, the functional thermally conductive filler is added into the interface adhesion promoter, ultrasonically dispersed at 45-50℃ for 30-50 min, filtered and dried to obtain activated modified thermally conductive filler; (2) Preparation of modified resin: According to the mass ratio (6-7):4, polyimide and polyvinyl butyral are put into a closed mixer and stirred for 2-3 hours at 180-185℃ and 200-300r / min. Then, the mixture is naturally cooled to 80-85℃ to obtain the modified resin. (3) Mixing and grinding: Add activated modified thermally conductive filler, organic functionalized nano filler, low-temperature toughening modifier, thermo-oxidative stabilizer and rheology modifier to the modified resin in sequence. After high-speed stirring and homogenization at 1500-2000r / min, send it to a sand mill for fine grinding for 35-45min. (4) Viscosity adjustment: Add mixed organic solvent to adjust the overall viscosity of the paint liquid, filter it with a 200-mesh filter to remove impurities, let it stand for 24-30 hours to defoam, and obtain the finished composite insulating paint.
[0016] A coating process for graphene copper wire composite insulation coating is divided into a graphene copper wire coating process and a superconducting wire coating process. The graphene copper wire coating process includes wire degreasing, acid pickling and neutralization, pure water cleaning, high-temperature drying, oxygen-argon mixed plasma surface activation, multi-pass continuous immersion coating, gradient segmented high-temperature curing, and cooling and wire winding. The superconducting wire coating process includes surface cleaning, low-temperature phosphating and passivation, drying and dehumidification, alternating layering of insulating varnish, medium-temperature curing, overall heat preservation and shaping, and inspection and winding.
[0017] The beneficial effects of this invention are as follows: In this invention, tetraethyl orthosilicate is used as the silicon source to prepare spherical nano-silica via a sol-gel method. The spherical nano-silica forms the core, with a nano-alumina transition shell coated on its surface. Through silane hydrolysis grafting, flexible organosilicon long-chain functional groups are grafted onto the outer side of the transition shell, forming a three-level composite structure of inorganic core-inorganic transition shell-flexible organic functional layer. Furthermore, after surface activation modification with a silane coupling agent, the surface exhibits a high density of active hydroxyl and epoxy active groups, resulting in particles that are non-agglomerated and exhibit excellent monodispersity. This allows the obtained organically functionalized nanofiller to be well dispersed in the resin matrix. By introducing organically functionalized nanofillers into the resin matrix… The nanofiller, with its surface-grafted organic functional layer carrying a large number of active hydroxyl and epoxy active groups, can undergo covalent cross-linking reactions with the metallic hydroxyl groups on the surface of the wire substrate, the oxygen-containing groups on the surface of graphene, and the copolymer active groups of the resin matrix during the curing process. This forms an integrated covalent bond network of "wire substrate-nanocomposite material-resin matrix," significantly improving the interfacial bonding strength and achieving high-strength adhesion and anchoring at the molecular level, thereby helping to improve the adhesion and stability of the paint film. Moreover, the highly dispersed organic functionalized nanofiller has an extremely small particle size, allowing it to penetrate and embed into the micropores on the surface of graphene copper wires and the microtextures of the superconducting wire substrate, forming micro-nanomechanical... The interlocking structure increases the effective contact area between the paint film and the substrate, thereby further improving the adhesion and peel strength of the paint film. Simultaneously, the flexible long chains of organosilicon on the surface of the organic functionalized nanofiller possess excellent ultra-low temperature flexibility. When the resin matrix shrinks and undergoes microscopic deformation at low temperatures, the flexible chain segments can absorb and release concentrated internal stress within the paint film through their own stretching, twisting, and sliding, preventing stress accumulation and the formation of microcracks. This plays a core role in micro-toughening and stress buffering, preventing microcracks in the paint film at ultra-low temperatures. Furthermore, the spherical nano-silica rigid core has an extremely low coefficient of thermal expansion at low temperatures, with almost no dimensional change under ultra-low temperature conditions, allowing for the construction of a stable rigid core within the paint film microstructure. The rigid support framework constrains the drastic low-temperature shrinkage behavior of the modified resin matrix, significantly reducing the overall low-temperature shrinkage rate of the paint film. This reduces the internal stress generated by shrinkage deformation at the source. Furthermore, a transition shell is formed between the rigid core and the flexible organic layer. Through the gradient transition of thermal expansion coefficient and mechanical modulus, the abrupt difference in physical properties between the inorganic rigid core and the organic flexible matrix is eliminated, transforming the original abrupt interfacial stress into a gentle gradient stress distribution. Moreover, the abundant surface hydroxyl groups of the alumina shell construct a dense covalent bonded interface, eliminating interfacial micropores and debonding defects, and preventing the initiation, propagation, and penetration of interfacial microcracks under ultra-low temperature conditions, thereby further avoiding the occurrence of low-temperature cracking of the paint film.
[0018] In this invention, the configured insulating composite coating uses modified resin as the film-forming main body, providing excellent film-forming properties, insulation, and basic adhesion. Functional thermally conductive fillers enhance the thermal conductivity and heat dissipation capacity of the coating film while ensuring insulation performance, preventing heat buildup in the wires. Organic functionalized nanofillers are the core functional components, simultaneously strengthening adhesion and ultra-low temperature crack resistance, improving the stability of the coating film. A low-temperature toughness modifier enhances the low-temperature chain activity of the resin matrix, achieving a balance between high and low temperature toughness in conjunction with the organic functionalized nanofillers. A thermo-oxidative stabilizing agent improves the high-temperature oxidation resistance and aging resistance of the coating film. The coating enhances chemical properties and expands the service temperature range. The interface adhesion promoter further optimizes the interfacial wettability between the substrate and the coating film, helping to improve the bonding strength. The rheology modifier optimizes the flowability and leveling of the coating, making it suitable for high-speed wire coating processes. The mixed organic solvent ensures uniform dispersion of each component, improving the density and smoothness of the coating film. This results in comprehensive performance such as high adhesion, ultra-low temperature crack resistance, high insulation, high thermal conductivity, and aging resistance. Moreover, the coating process is simple, suitable for industrial mass production, and has a wide range of applications, possessing extremely high market promotion value and industrial application prospects. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] In this embodiment of the invention, the functional thermally conductive filler is composed of graphene nanosheets, nano-alumina, and hexagonal boron nitride in a mass ratio of 1:1:1.5. The low-temperature toughening modifier is carboxyl-terminated butadiene-acrylonitrile rubber; The thermo-oxidative stabilizer is nano-cerium dioxide powder; The interfacial adhesion promoter is silane coupling agent KH-560; The rheology modifier is fumed silica; The mixed organic solvent is prepared by combining N-methylpyrrolidone and xylene in a volume ratio of 2:1.
[0021] In this embodiment of the invention, the graphene copper wire coating process is as follows: 1. Substrate pretreatment: 1.0mm diameter graphene composite copper wire is degreased with 5% sodium hydroxide hot alkaline solution, neutralized and cleaned with dilute sulfuric acid, rinsed with pure water, and dried at 110℃. 2. Surface activation: Oxygen-argon mixed plasma treatment for 2 minutes reduces the surface contact angle and improves the wettability of the paint. 3. Continuous coating: A vertical continuous coating machine is used to uniformly coat three layers of insulating varnish, with a single layer wet film thickness of 8μm; 4. Gradient curing: The first stage is pre-cured at 180℃ for 30 minutes, and the second stage is fully cured at 220℃ for 60 minutes; 5. Cooling and winding: Wind up the wire after it has cooled to room temperature.
[0022] In this embodiment of the invention, the coating process for superconducting wires is as follows: 1. Substrate pretreatment: Degreasing and cleaning of NbTi superconducting wires and YBCO superconducting tapes, low-temperature phosphating passivation treatment with manganese, and low-temperature drying at 80℃; 2. Layered coating: The composite insulating enamel is applied in 12 alternating coats using a horizontal uniform-speed dip-coating device; 3. Low-temperature curing in each coat: After each coat is applied, bake at a constant temperature of 120℃ for 15 minutes. High-temperature rapid curing is prohibited. 4. Post-coating setting: After all coating is completed, maintain the overall temperature at 100℃ for 40 minutes and allow it to cool naturally. 5. Inspection and winding: After passing the inspection, the roll is wound up.
[0023] Example 1 A graphene-copper wire composite insulating varnish is composed of the following raw materials in parts by weight: 56 parts modified resin, 11 parts functional thermally conductive filler, 5 parts organic functionalized nanofiller, 3 parts low-temperature toughening modifier, 2 parts thermo-oxidative stabilizing agent, 1 part interface adhesion promoter, 0.4 parts rheology modifier, and 32 parts mixed organic solvent. The specific preparation method includes the following steps: (1) Powder modification pretreatment: According to the weight parts, the functional thermally conductive filler was added into the interface adhesion promoter, ultrasonically dispersed at 45℃ for 30 min, filtered and dried to obtain the activated modified thermally conductive filler. (2) Preparation of modified resin: Polyimide and polyvinyl butyral were put into a closed mixer at a mass ratio of 6:4 and stirred for 2 hours at 180°C and 200r / min. Then the mixture was allowed to cool naturally to 80°C to obtain the modified resin. (3) Mixing and grinding: Add activated modified thermally conductive filler, organic functionalized nano filler, low-temperature toughening modifier, thermo-oxidative stabilizer and rheology modifier to the modified resin in sequence. After high-speed stirring and homogenization at 1500r / min, send it to a sand mill for fine grinding for 35min. (4) Viscosity adjustment: Add mixed organic solvent to adjust the overall viscosity of the paint liquid, filter it with a 200-mesh filter to remove impurities, let it stand for 24 hours to defoam, and obtain the finished composite insulating paint coating.
[0024] The preparation method of the organic functionalized nanofiller is as follows: 1) Measure anhydrous ethanol and ultrapure water at a volume ratio of 8:2 and add them to the reaction vessel in sequence. Stir thoroughly at room temperature and slowly add 14 mol / L ammonia water to adjust the pH of the system to 10.5 to obtain a buffer solution. Then, add tetraethyl orthosilicate dropwise to the buffer solution at a mass ratio of 1:10 at a dropping rate of 1.0 mL / min and stir until homogeneous to obtain the reaction solution. 2) Transfer the reaction solution to the reaction vessel, seal it, and stir it at 400 r / min for 4 h at a constant temperature of 25℃. After the reaction is completed, centrifuge it, wash it repeatedly with anhydrous ethanol and deionized water, and then dry it to obtain spherical nano-silica. 3) Spherical nano-silica was ultrasonically dispersed in a mixed solvent of anhydrous ethanol and ultrapure water at a volume ratio of 5:1 to obtain a dispersion with a solid content of 5wt%. Then, a 10% sec-butoxide aluminum ethanol solution was added dropwise to the dispersion at a mass ratio of 0.8:1 and a dropping rate of 0.8 mL / min. Simultaneously, ammonia water with a concentration of 2 mol / L was slowly added dropwise to adjust the pH to 8.5. The temperature was then raised to 55℃ and the reaction was stirred at a constant temperature of 30 r / min for 3 h. After the reaction was completed, the mixture was centrifuged, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a silica composite alumina intermediate. 4) The silica-alumina composite intermediate was dispersed in anhydrous toluene solvent to obtain a suspension with a mass fraction of 8%. Then, according to the mass ratio of modifier to silica-alumina composite intermediate of 1:4, the modifier obtained by compounding methyltriethoxysilane and 3-glycidyl etheroxypropyltriethoxysilane at a mass ratio of 2:1 was slowly added to the suspension. After thorough stirring, the mixture was placed in a reaction vessel and heated to 80°C in a high-purity nitrogen atmosphere. The mixture was then stirred in a closed container at 350 r / min for 4 h. 5) After the reaction is complete, allow the mixture to cool naturally to room temperature. After centrifugation, wash the mixture repeatedly with anhydrous ethanol and deionized water. Then, spread the resulting product evenly in a crucible and place it in a vacuum drying oven. Anneal the product at 120°C and a vacuum degree ≤ -0.09 MPa for 2 hours. After ultrafine grinding, pass the product through a 2000-mesh sieve to obtain the desired organic functionalized nanofiller.
[0025] Example 2 A graphene-copper wire composite insulating varnish is composed of the following raw materials in parts by weight: 60 parts modified resin, 15 parts functional thermally conductive filler, 7 parts organic functionalized nanofiller, 5 parts low-temperature toughening modifier, 3 parts thermo-oxidative stabilizing agent, 1.5 parts interface adhesion promoter, 1.2 parts rheology modifier, and 40 parts mixed organic solvent. The specific preparation method includes the following steps: (1) Powder modification pretreatment: According to the weight parts, the functional thermally conductive filler was added into the interface adhesion promoter, ultrasonically dispersed at 46℃ for 40 min, filtered and dried to obtain the activated modified thermally conductive filler. (2) Preparation of modified resin: Polyimide and polyvinyl butyral were put into a closed mixer at a mass ratio of 6.5:4 and stirred for 2.5 h at 182℃ and 250 r / min. Then the mixture was allowed to cool naturally to 82℃ to obtain the modified resin. (3) Mixing and grinding: Add activated modified thermally conductive filler, organic functionalized nano filler, low-temperature toughening modifier, thermo-oxidative stabilizer and rheology modifier to the modified resin in sequence. After high-speed stirring and homogenization at 1800r / min, send it to a sand mill for fine grinding for 40min. (4) Viscosity adjustment: Viscosity adjustment: Add mixed organic solvent to adjust the overall viscosity of the paint liquid, filter it with a 200-mesh filter to remove impurities, let it stand for 28 hours to defoam, and obtain the finished composite insulating paint coating.
[0026] The preparation method of the organic functionalized nanofiller is as follows: 1) Measure anhydrous ethanol and ultrapure water at a volume ratio of 9:2 and add them to the reaction vessel in sequence. Stir thoroughly at room temperature and slowly add 15 mol / L ammonia water to adjust the pH of the system to 11.0 to obtain a buffer solution. Then, at a mass ratio of 1:11, slowly add tetraethyl orthosilicate to the buffer solution at a dropping rate of 1.5 mL / min and stir until homogeneous to obtain the reaction solution. 2) Transfer the reaction solution to the reaction vessel, seal it, and stir it at 450 r / min for 5 h at a constant temperature of 26℃. After the reaction is completed, centrifuge it, wash it repeatedly with anhydrous ethanol and deionized water, and then dry it to obtain spherical nano-silica. 3) Spherical nano-silica was ultrasonically dispersed in a mixed solvent of anhydrous ethanol and ultrapure water at a volume ratio of 5.5:1 to obtain a dispersion with a solid content of 7wt%. Then, an 11% sec-butoxide aluminum ethanol solution was added dropwise to the dispersion at a mass ratio of 0.9:1 and a dropping rate of 0.9 mL / min. Simultaneously, ammonia water with a concentration of 2.5 mol / L was slowly added dropwise to make the pH value 9.0. Then, the temperature was raised to 56℃ and the reaction was stirred at a constant temperature of 40 r / min for 4 h. After the reaction was completed, the mixture was separated by centrifugation, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a silica composite alumina intermediate. 4) The silica-alumina composite intermediate was dispersed in anhydrous toluene solvent to obtain a suspension with a mass fraction of 9%. Then, according to the mass ratio of modifier to silica-alumina composite intermediate of 1:5, the modifier obtained by compounding methyltriethoxysilane and 3-glycidyl etheroxypropyltriethoxysilane at a mass ratio of 2.3:1 was slowly added to the suspension. After thorough stirring, the mixture was placed in a reaction vessel and heated to 85°C in a high-purity nitrogen atmosphere. The mixture was then stirred in a closed container at 400 r / min for 5 h. 5) After the reaction is complete, allow the mixture to cool naturally to room temperature. After centrifugation, wash the mixture repeatedly with anhydrous ethanol and deionized water. Then, spread the resulting product evenly in a crucible and place it in a vacuum drying oven. Anneal the product at 123°C and a vacuum degree ≤ -0.09MPa for 2.5 hours. After ultrafine grinding, pass the product through a 2000-mesh sieve to obtain the desired organic functionalized nanofiller.
[0027] Example 3 A graphene-copper wire composite insulating varnish is composed of the following raw materials in parts by weight: 64 parts modified resin, 18 parts functional thermally conductive filler, 10 parts organic functionalized nanofiller, 6 parts low-temperature toughening modifier, 5 parts thermo-oxidative stabilizing agent, 2.5 parts interface adhesion promoter, 1.6 parts rheology modifier, and 46 parts mixed organic solvent. The specific preparation method includes the following steps: (1) Powder modification pretreatment: According to the weight parts, the functional thermally conductive filler was added into the interface adhesion promoter, ultrasonically dispersed at 50℃ for 50 min, filtered and dried to obtain the activated modified thermally conductive filler. (2) Preparation of modified resin: Polyimide and polyvinyl butyral were put into a closed mixer at a mass ratio of 7:4 and stirred for 3 hours at 185°C and 300 r / min. Then the mixture was allowed to cool naturally to 85°C to obtain the modified resin. (3) Mixing and grinding: Add activated modified thermally conductive filler, organic functionalized nanofiller, low-temperature toughening modifier, thermo-oxidative stabilizer and rheology modifier to the modified resin in sequence. After high-speed stirring and homogenization at 2000r / min, send it to a sand mill for fine grinding for 45min. (4) Viscosity adjustment: Add mixed organic solvent to adjust the overall viscosity of the paint liquid, filter it with a 200-mesh filter to remove impurities, let it stand for 30 hours to defoam, and obtain the finished composite insulating paint.
[0028] The preparation method of the organic functionalized nanofiller is as follows: 1) Measure anhydrous ethanol and ultrapure water at a volume ratio of 10:3 and add them to the reaction vessel in sequence. Stir thoroughly at room temperature and slowly add 16 mol / L ammonia water to adjust the pH of the system to 11.0 to obtain a buffer solution. Then, at a mass ratio of 1:12, slowly add tetraethyl orthosilicate to the buffer solution at a dropping rate of 2.0 mL / min and stir until homogeneous to obtain the reaction solution. 2) Transfer the reaction solution to the reaction vessel, seal it, and stir it at 500 r / min for 6 h at a constant temperature of 28℃. After the reaction is completed, centrifuge it, wash it repeatedly with anhydrous ethanol and deionized water, and then dry it to obtain spherical nano-silica. 3) Spherical nano-silica was ultrasonically dispersed in a mixed solvent of anhydrous ethanol and ultrapure water at a volume ratio of 6:1 to obtain a dispersion with a solid content of 8wt%. Then, a 12% sec-butoxide aluminum ethanol solution was added dropwise to the dispersion at a mass ratio of 0.9:1 and a dropping rate of 0.9 mL / min. Simultaneously, ammonia water with a concentration of 3 mol / L was slowly added dropwise to make the pH value 9.0. Then, the temperature was raised to 60℃ and the reaction was stirred at a constant temperature of 50 r / min for 5 h. After the reaction was completed, the mixture was separated by centrifugation, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a silica composite alumina intermediate. 4) The silica-alumina composite intermediate was dispersed in anhydrous toluene solvent to obtain a suspension with a mass fraction of 10%. Then, according to the mass ratio of modifier to silica-alumina composite intermediate of 1:6, the modifier obtained by compounding methyltriethoxysilane and 3-glycidyl etheroxypropyltriethoxysilane at a mass ratio of 2.5:1 was slowly added to the suspension. After thorough stirring, the mixture was placed in a reaction vessel and heated to 90°C in a high-purity nitrogen atmosphere. The mixture was then stirred in a closed container at 400 r / min for 6 h. 5) After the reaction is complete, allow the mixture to cool naturally to room temperature. After centrifugation, wash the mixture repeatedly with anhydrous ethanol and deionized water. Then, spread the resulting product evenly in a crucible and place it in a vacuum drying oven. Anneal the product at 125°C and a vacuum degree ≤ -0.09 MPa for 3 hours. After ultrafine grinding, pass the product through a 2000-mesh sieve to obtain the desired organic functionalized nanofiller.
[0029] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain organic functionalized nanofillers.
[0030] Comparative Example 2: This comparative example is basically the same as Example 1, except that steps 1)-2) are omitted in the preparation of the organic functionalized nanofiller.
[0031] Comparative Example 3: This comparative example is basically the same as Example 1, except that step 3 is omitted in the preparation of the organic functionalized nanofiller.
[0032] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 4 is omitted in the preparation of the organic functionalized nanofiller.
[0033] Comparative Example 5: This comparative example is basically the same as Example 1, except that steps 3)-5) are omitted in the preparation of the organic functionalized nanofiller.
[0034] Test experiment: Composite insulating enamel samples were prepared using the methods of Examples 1-3 and Comparative Examples 1-5. Then, the graphene copper wire enamel coating process disclosed in this invention was used to coat the composite insulating enamel samples onto a graphene composite copper wire with a diameter of 1.0 mm. After the enamel film was completely cured, adhesion test, thermal conductivity test, thermal aging performance test and ultra-low temperature crack resistance test were performed respectively. The test results are shown in Table 1. Adhesion testing shall be conducted in accordance with GB / T9286-1998 "Cross-cut test for paint and varnish films"; Thermal conductivity was tested according to ASTM D5470, "Standard Test Method for Testing Thermal Conductivity Using Steady-State Heat Flow Metering," using the heat flow method to test the thermal conductivity of the paint film. For the thermal aging performance test, refer to GB / T 4074.6-2024 "Test methods for winding wires - Part 6: Thermal properties", and keep the enameled wire at 240℃ for 30 minutes. After cooling, observe the cracking of the enamel film. The ultra-low temperature crack resistance test was conducted in accordance with GB / T 4074.4-2024 "Test Methods for Winding Wires - Part 4: Chemical Properties". The enameled wire was subjected to a refrigerant resistance test in the low temperature refrigerant R134a medium, and the cracking of the enamel film was observed. Table 1
[0035] As shown in Table 1, the composite insulating coating of this invention has high adhesion, high thermal conductivity, aging resistance and ultra-low temperature crack resistance. Moreover, the coating process is simple, suitable for industrial mass production, and has a wide range of applications, with extremely high market promotion value and industrial application prospects.
[0036] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A graphene-copper wire composite insulating coating, characterized in that, The composite insulating coating is composed of the following raw materials in parts by weight: 56-64 parts modified resin, 11-18 parts functional thermally conductive filler, 5-10 parts organic functionalized nanofiller, 3-6 parts low-temperature toughening modifier, 2-5 parts thermo-oxidative stabilizing agent, 1-2.5 parts interface adhesion promoter, 0.4-1.6 parts rheology modifier, and 32-46 parts mixed organic solvent.
2. The graphene-copper wire composite insulating coating according to claim 1, characterized in that, The modified resin is a blend of polyimide and polyvinyl butyral; The functional thermally conductive filler is composed of graphene nanosheets, nano-alumina, and hexagonal boron nitride in a mass ratio of 1:1:(1.0-1.8). The low-temperature toughness modifier is carboxyl-terminated butadiene-acrylonitrile rubber; The thermo-oxidative stabilizer is nano-cerium dioxide powder; The interface adhesion promoter is silane coupling agent KH-560; The rheology modifier is fumed silica. The mixed organic solvent is prepared by combining N-methylpyrrolidone and xylene in a volume ratio of (2.0-2.5):
1.
3. The graphene-copper wire composite insulating coating according to claim 1, characterized in that, The preparation method of the organic functionalized nanofiller is as follows: 1) Spherical nano-silica is ultrasonically dispersed in a mixed solvent to obtain a dispersion with a solid content of 5-8 wt%. Then, a 10-12% (w / w) aluminum sec-butoxide ethanol solution is slowly added dropwise to the dispersion, and a 2-3 mol / L ammonia solution is added dropwise simultaneously to adjust the pH to 8.5-9.
0. The temperature is then raised to 55-60℃ and stirred for 3-5 hours. After the reaction is completed, the mixture is centrifuged, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a silica composite alumina intermediate. 2) Disperse the silica-alumina composite intermediate in anhydrous toluene solvent to obtain a suspension with a mass fraction of 8-10%. Slowly add the weighed modifier to the suspension, stir thoroughly, and place it in a reaction vessel. In a high-purity nitrogen atmosphere, heat to 80-90℃ and stir in a closed container at 350-400 r / min for 4-6 h. 3) After the reaction is complete, allow the mixture to cool naturally to room temperature. After centrifugation, wash the mixture repeatedly with anhydrous ethanol and deionized water. Then, spread the obtained product evenly in a crucible and place it in a vacuum drying oven. Perform constant temperature vacuum annealing for 2-3 hours. After ultrafine grinding, pass the product through a 2000-mesh sieve to obtain the desired organic functionalized nanofiller.
4. The graphene-copper wire composite insulating coating according to claim 3, characterized in that, In step 1), the mixed solvent is composed of anhydrous ethanol and ultrapure water in a volume ratio of (5-6):1; The mass ratio of the sec-butoxide aluminum ethanol solution to the dispersion is (0.8-0.9):1; The slow dripping rate is 0.8-0.9 mL / min; The rotation speed of the constant-temperature stirring reaction is 30-50 r / min.
5. The graphene-copper wire composite insulating coating according to claim 3, characterized in that, In step 2), the modifier is obtained by compounding methyltriethoxysilane and 3-glycidyl etheroxypropyltriethoxysilane in a mass ratio of (2.0-2.5):1; The mass ratio of the modifier to the silica-alumina composite intermediate is 1:(4-6). The stirring speed is 350-400 r / min.
6. The graphene-copper wire composite insulating coating according to claim 3, characterized in that, In step 3), the temperature of the vacuum annealing process is 120-125℃, and the vacuum degree is ≤-0.09MPa.
7. The graphene-copper wire composite insulating coating according to claim 3, characterized in that, The method for preparing the spherical nano-silica is as follows: 1) Measure anhydrous ethanol and ultrapure water, add them to the reaction vessel in sequence, stir thoroughly at room temperature, and slowly add ammonia water with a concentration of 14-16 mol / L to adjust the pH of the system to 10.5-11.0 to obtain a buffer solution. Then slowly add tetraethyl orthosilicate to the buffer solution and stir evenly to obtain the reaction solution. 2) Transfer the reaction solution to a reaction vessel, seal it, and stir the reaction at a constant temperature of 25-28℃ for 4-6 hours. After the reaction is completed, separate it by centrifugation, wash it repeatedly with anhydrous ethanol and deionized water, and then dry it to obtain spherical nano-silica.
8. The graphene-copper wire composite insulating coating according to claim 7, characterized in that, The volume ratio of anhydrous ethanol to ultrapure water is (8-10):(2-3); The mass ratio of tetraethyl orthosilicate to buffer solution is 1:(10-12). The slow dripping rate is 1.0-2.0 mL / min; The stirring speed is 400-500 r / min.
9. A method for preparing a graphene-copper wire composite insulating coating according to any one of claims 1-8, characterized in that, Specifically, the steps include the following: (1) Powder modification pretreatment: According to the weight parts, the functional thermally conductive filler is added into the interface adhesion promoter, ultrasonically dispersed at 45-50℃ for 30-50 min, filtered and dried to obtain activated modified thermally conductive filler; (2) Preparation of modified resin: According to the mass ratio (6-7):4, polyimide and polyvinyl butyral are put into a closed mixer and stirred for 2-3 hours at 180-185℃ and 200-300r / min. Then, the mixture is naturally cooled to 80-85℃ to obtain the modified resin. (3) Mixing and grinding: Add activated modified thermally conductive filler, organic functionalized nano filler, low-temperature toughening modifier, thermo-oxidative stabilizer and rheology modifier to the modified resin in sequence. After high-speed stirring and homogenization at 1500-2000r / min, send it to a sand mill for fine grinding for 35-45min. (4) Viscosity adjustment: Add mixed organic solvent to adjust the overall viscosity of the paint liquid, filter it with a 200-mesh filter to remove impurities, let it stand for 24-30 hours to defoam, and obtain the finished composite insulating paint.
10. The coating process for graphene-copper wire composite insulation enamel according to any one of claims 1-8, characterized in that, It is divided into graphene copper wire coating process and superconducting wire coating process; The graphene copper wire coating process includes wire degreasing, acid pickling and neutralization, pure water cleaning, high-temperature drying, oxygen-argon mixed plasma surface activation, multi-pass continuous immersion coating, gradient segmented high-temperature curing, and cooling and wire winding. The superconducting wire coating process includes surface cleaning, low-temperature phosphating and passivation, drying and dehumidification, layered alternating impregnation with insulating varnish, medium-temperature curing, overall heat preservation and shaping, and inspection and winding.